5t-4+3t=4(2t-1)

Simple and best practice solution for 5t-4+3t=4(2t-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t-4+3t=4(2t-1) equation:


Simplifying
5t + -4 + 3t = 4(2t + -1)

Reorder the terms:
-4 + 5t + 3t = 4(2t + -1)

Combine like terms: 5t + 3t = 8t
-4 + 8t = 4(2t + -1)

Reorder the terms:
-4 + 8t = 4(-1 + 2t)
-4 + 8t = (-1 * 4 + 2t * 4)
-4 + 8t = (-4 + 8t)

Add '4' to each side of the equation.
-4 + 4 + 8t = -4 + 4 + 8t

Combine like terms: -4 + 4 = 0
0 + 8t = -4 + 4 + 8t
8t = -4 + 4 + 8t

Combine like terms: -4 + 4 = 0
8t = 0 + 8t
8t = 8t

Add '-8t' to each side of the equation.
8t + -8t = 8t + -8t

Combine like terms: 8t + -8t = 0
0 = 8t + -8t

Combine like terms: 8t + -8t = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x+x*0.12=6273.53 | | -7(x+2)-16=18+1 | | X+(2x-3)=72 | | 3+(15-1)(-4/3) | | 5y-2=29-4y | | 6=6+y | | 5(-3+7x)=-330 | | x+x*0.09=1000 | | 2(0.3r+1)=24 | | x-1/3=4/3 | | 5x+1=43-2x | | 2x^2+5x+6=x^2 | | 21x-16y=120 | | 10x-42+17x=13+14 | | .0855t^2-.916t+1.737=0 | | 8+2t-2=7t+8-4t | | 3(X+2)(X+2)+16(X+2)+5= | | 3+(5x-6/4) | | 3mx-9y=2(m+2b) | | x-7=144 | | 4s^2+16s-as-4a= | | 2/3(3/5) | | (5/6)t+4=(1/6)t-2 | | 13x+3x-5=27 | | .0825t^2-.886t+1.752=0 | | 5x-15=x+25 | | -x^2+11=0 | | -8+x/8=-12 | | 6(6x+5)=-390 | | (10)+c^3/3=c^3/(3)+10 | | 6x+3=4x+7 | | 3x^2+5x+343=0 |

Equations solver categories